The Implementation of Fiqh Principle in Islamic Financial Products: A Systematic Literature Review - Nafisatu Roudlotin Ni’mah; Asmuni (Faculty of Economics and Management, 2024)
The fiqh rules aims to provide a foundation for all activities carried out by Muslims, including economic activities. The rules of fiqh can solve various contemporary economic problems by drawing a red thread from the previous arguments. For example, the phenomenon of online buying and selling that is currently rife can be found by linking the arguments that can be used as a reference. This implementation must be done because, with it, Islamic economic activity will be more straightforward to achieve its goals. The purpose of this study is to find out the application of the rules of fiqh in various Islamic financial products. The method used in this study is a systematic literature review which is done extracting several scientific journals related to the theme. The application of the rules of fiqh in various Islamic financial products has proven to be significant and had a positive impact on various economic sides. Applying the rules of fiqh gives all economic layers a foundation for doing something so that it does not come out of the principles of Islamic sharia.